2021
DOI: 10.1186/s12877-021-02477-3
|View full text |Cite
|
Sign up to set email alerts
|

Building the capacity of community health workers to support health and social care for dependent older people in Latin America: a pilot study in Fortaleza, Brazil

Abstract: Background Brazil is seeing rapid population ageing, which is leading to new demands on primary health care services. There is a need to develop and assess the effectiveness of new interventions to build the capacity of staff, including community health workers, to meet the needs of groups such as care-dependent older people and their care-givers. This study examines the feasibility of a small training intervention piloted in the Brazilian city of Fortaleza. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Task-sharing interventions in low- and middle-income countries have similarly been shown to be effective at reducing systolic and diastolic blood pressure [ 68 ], and lowering low-density lipoprotein cholesterol [ 69 ], though further studies are needed to ascertain their role in managing diabetes mellitus [ 70 ]. Training community health workers to care for dependent older populations has been demonstrated to be both feasible and effective in other contexts [ 71 ], and should be explored as a cost-effective intervention among older Syrian refugees in Lebanon. Further, as informal caregiving is overwhelmingly gendered both in the Arab region and globally [ 72 ], training and compensating caregivers would additionally address economic gender disparities in labour force participation [ 26 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Task-sharing interventions in low- and middle-income countries have similarly been shown to be effective at reducing systolic and diastolic blood pressure [ 68 ], and lowering low-density lipoprotein cholesterol [ 69 ], though further studies are needed to ascertain their role in managing diabetes mellitus [ 70 ]. Training community health workers to care for dependent older populations has been demonstrated to be both feasible and effective in other contexts [ 71 ], and should be explored as a cost-effective intervention among older Syrian refugees in Lebanon. Further, as informal caregiving is overwhelmingly gendered both in the Arab region and globally [ 72 ], training and compensating caregivers would additionally address economic gender disparities in labour force participation [ 26 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, it was reported that offering training to CHWs enhanced their capacity to meet new health challenges which are rapidly emerging. This kind of training should focus on the training needs for CHWs related to the needs of healthcare that they are dealing with in their respective communities [ 36 ]. Implementing training needs-based programs for CHWs was also reported in another study as an intervention to help fill gaps in effectively providing health services such as mental healthcare in underserved U.S. Latino communities [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Capacity building of community health care workers in Brazil yielded in the successful conduct of the home visits and screening for risk factors in the elderly population (Neto et al, 2021). Nurses play a vital role in the care of patients especially caring for those who are dying, hence it is imperative for them to know the best principles of palliative care (Sadhu, Salins, & Kamath, 2010).…”
Section: Introductionmentioning
confidence: 99%